Usulan Aplikasi Metode Material Requirement Planning (MRP) dalam Perencanaan Kebutuhan Firebrick PT Semen Padang - Fajar Aristiyanto; Nilda Tri Putri; Alexie Herryandie Bronto Adi (Jurnal Optimasi Sistem Industri, 2016)
The purpose of this article is to describe the results of research models firebrick requirements planning in PT Semen Padang with MRP method. Firebrick is one of the spare parts and essential in the production of operational PT Semen Padang as protective and insulating of shell kiln. This article describes the firebrick requirements planning at all kiln Indarung II / III, IV and V to meet the needs of 2017 up to 2018. One type of firebrick most widely used in PT Semen Padang is spinal firebrick. Spinal firebrick highly susceptible to hydration and moisture as the main component is MgO compound that is hygroscopic so susceptible to damage in the form of cracks firebrick. Based on the research that has been done, get MRP application design that can be used in planning the needs of firebrick PT Semen Padang to come. Plans need firebrick for compliance in 2017 to 2018 : (a) item 422 purchased through two phases in the 4th month of 12.711 pcs and in the 9th month of 24.909 pcs (b) item 622 purchased through two phases in the 4th month of 21.185 pcs and in the 9th month of 41.515 pcs (c) item P22 purchased through two phases in the 4th month of 446 pcs and in the 9th month of 874 pcs (d) item P + 22 purchased through two phases in the 4th month of 446 pcs and in the 9th month of 874 pcs (e) item 425 purchased in the 8th month of 14.626 pcs (f) item 825 purchased in the 8th month of 20.600 pcs (g) P25 item purchased in the 8th month of 412 pcs (h) P + 25 items purchased in the 8th month of 412 pcs.